Engineering methods in fire protection design (Academic Journal of Internal Affairs, 2020)
Designs, and so is fire protection design, are accomplished by several methods. Two basic design methods can be differentiated, one of them is based on descriptive regulation and the other is the engineering method. Both methods have advantages and disadvantages. The complex design tasks can be solved by engineering method effectively. Modelling as a scientific tool can be used for fulfilment requirements of analysis and confirmation. Several models are used for fire protection design. These models can be physical, deterministic and stochastic ones. A typical example of engineering methods applied in fire protection is the use of computer simulation. The two main scopes are here fire models and evacuation models. Evacuation models make control of the evacuation concept of planned building possible. In evacuation models can be physical parameters and behaviour patterns set. The fire and smoke spreading simulation can verify the smoke and heat dissipation system. Buildings can be analysed in complexity and changes of many parameters can be monitored. The most important of these are temperature values and visibility in smoke. From 2015 the national fire protection regulations made wider application of engineering methods possible. Simulation methods have been spreading and more and more of them are approved year by year. The fire protection authority has an important role in the design process already by supporting the correct choice of basic design data at consultations. Very important became the awareness of the authority on IT area, too.
Keywords: fire prevention; engeneering methods; design; authority